The Effect of Adding Oak Bark Powder to the Diet on Some Productive and Immunological Characteristics of Broiler Chicks - Hammod , Ali J.; Alshukri, Aqeel Y.; Areaaer, Ammar H.; Alfertosi, Khalil A.; Alyasari, Ali F. (International Journal of Poultry Science, 2018)
Background and Objective: The current study investigated whether the addition of oak bark powder to poultry diets improved the production and immunological traits of broilers. The goal of farmers is to increase immunity to reduce the risk of different diseases and reduce the use of antibiotics, which negatively affect human and animal health. The attainment of this goal leads to an increase in profits for the broiler industry. We aimed to study the effect of oak bark powder on the productive, physiological and immunological characteristics of broiler chicks. Methodology: A total of 180 unsexed Ross chicks (initial weight of 41 g per chick) were raised in a closed house that was divided into pens, each of which was 3 m2 and the chicks were randomly distributed to the pens. Four treatments with 45 chicks each were tested. Three replicates were carried out for each treatment. Results: The results showed that there were no significant differences in the final body weight, cumulative weight gain, total feed intake, total feed conversion ratio, mortality rate, economic figure and hemoglobin level of the chicks. However, the addition of oak powder had a significant effect on decreasing the incidence of Newcastle disease and infectious bursal disease. There was a significant increase in the number of blood cells for all levels of oak powder addition, resulting in a significant improvement in the number of red blood cells of the broiler chicks fed the 3% oak bark powder and a significant improvement in the number of white blood cells of the broiler chicks fed the 1% oak bark powder. Conclusion: Because the addition of oak bark powder improved the immunological and blood parameters of broiler chicks, it is recommended to add oak bark powder to broiler chick diets to enhance immunity and improve blood parameters in broiler chicks.